Do Current Asthma-Preventive Measures Appropriately Face the World Health Organization's Concerns: A Study Presentation of a New Clinical, Prospective, Multicentric Pediatric Asthma Exacerbation Cohort in Germany - Aydin, Malik; Naumova, Ella A.; Lutz, Soeren; Meyer-Bahlburg, Almut; Arnold, Wolfgang H.; Kreppel, Florian; Ehrhardt, Anja; Postberg, Jan; Wirth, Stefan (Frontiers in Pediatrics, 2020)
In summer 2017, the World Health Organization published 10 facts on asthma, which is known as a major non-communicable disease of high clinical and scientific importance with currently several hundred million people—with many children among them—suffering from air passages inflammation and narrowing. Importantly, the World Health Organization sees asthma as being underdiagnosed and undertreated. Consequently, much more efforts in clinical disease management and research need to be spent on reducing the asthma-related health burden. Particularly, for young approximately 6 months aged patients presenting recurrent bronchitic respiratory symptoms, many parents anxiously ask the doctors for risk prognosis for their children's future life. Therefore, we urgently need to reevaluate if the current diagnostic and treatment measures are in concordance with our yet incomplete knowledge of pathomechanisms on exacerbation. To contribute to this increasing concern worldwide, we established a multicentric pediatric exacerbation study network, still recruiting acute exacerbated asthmatics (children >6 years) and preschool asthmatics/wheezers (children <6 years) since winter 2018 in Germany. The current study that has a currently population comprising 176 study participants aims to discover novel holistic entry points for achieving a better understanding of the poorly understood plasticity of involved molecular pathways and to define biomarkers enabling improved diagnostics and therapeutics. With this study description, we want to present the study design, population, and few ongoing experiments for novel biomarker research. Clinical Trial Registration: German Clinical Trials Register (Deutsches Register für Klinische Studien, DRKS): DRKS00015738.